Binary Decavanadate‐Betaine Composite Materials of Potential Anticarcinogenic Activity1. Issue 8 (7th June 2013) - Kioseoglou, Efrosini; Gabriel, Catherine; Petanidis, Savvas; Psycharis, Vassilis; Raptopoulou, Catherine P.; Terzis, Aris; Salifoglou, Athanasios
Abstract Poised to investigate the association of vanadium with physiological substrates in materials capable of exerting anticancer biological activity, pH‐specific synthetic chemical reactivity between vanadium and triethyl ammonium acetate/trigonelline in aqueous and mixed organic‐aqueous media led to the isolation of three new binary composite materials, namely K2[(MeN(+)C5H4COOH)2][V10O28H2]·2H2O (1), [(H2N(+)Me2)4][V10O28H2][Me3N(+)CH2COO(–)]2 (2), and [(Me3N(+)CH2COOH)4][V10O28H2][Me3N(+)CH2COO(–)]2·2H2O (3). 1–3 were characterized by elemental analysis, FT‐IR and UV/Vis spectroscopy, Cyclic voltammetry, TGA‐DTG, and X‐ray crystallography. In all three compounds, the [V10O28H2]4– core unit is a common cluster assembly, with the vanadium in the +5 oxidation state. The counteracting cationic assembly in each composite material originates in the betaine starting reagent or the solvent out of which the materials crystallized. Biological activity studies of 1 and 3 in vitro in MCF‐7 breast epithelial and A549 lung adenocarcinoma cell cultures show that both materials inhibit the viability of both cell lines in a dose‐dependent fashion, in juxtaposition to the behavior of the betaine components present in these materials. Collectively, the herein studies a) reveal the uniquely defined synthetic methodologies and physicochemical properties of the variably assembled [V10O28H2]4– core units crystallized into the composite binary polyoxovanadate‐betaine lattice structures, b) unravel the distinct cytotoxicity profile of the composite materials toward MCF‐7 and A549 cells, and c) attest to their future potential as metallodrugs of pharmacological significance in anticancer activity.